Islamic Financial System Maturity in the Digital Age: A Comparative Institutional Analysis of Indonesia and South Korea - Talitha Anisya Rahma; Geesun Lee (Fakultas Ekonomi dan Bisnis Universitas Jenderal Soedirman, 2025)
Digital transformation has altered the structure and governance of financial systems, including Islamic finance, where institutional capacity and Sharia governance determine system sustainability. Existing studies emphasize that Islamic financial system maturity should be assessed beyond quantitative indicators by incorporating regulatory coherence, institutional effectiveness, and governance readiness in the digital era. This study aims to analyze the maturity of Islamic financial systems in Indonesia and South Korea from a comparative institutional perspective. Using a qualitative literature review method, this study positions the Islamic financial system at the country level as the unit of analysis and compares both countries across regulatory frameworks, institutional structures, and Sharia governance arrangements. Indonesia represents a Muslim-majority country with expanding Islamic finance activities, while South Korea offers insight into Islamic finance development within a non-Muslim-majority institutional context. The findings suggest that Indonesia demonstrates strong market potential but faces challenges related to regulatory integration, whereas South Korea exhibits a more selective and institution-driven approach to Sharia-compliant finance. These differences indicate that Islamic financial system maturity is shaped by institutional design and regulatory context rather than market size alone. This study concludes that an institutional perspective provides a more comprehensive framework for understanding Islamic financial system maturity in the digital age.